Sovra(bbon)Dante : riscritture e rimediazioni della Commedia nel settimo centenario della morte di Dante - Valentina Rovere (Perspectives Médiévales)
Within the rewritings of Dante’s Commedia published in 2021 three different trends can be highlighted : the aim (using modern tools to re-tell Dante’s poem), the audience of recipients (students of all ages), the remediation of all the three canticles. This paper takes into consideration five different case-studies to investigate the different strategies put forth by these authors, marking at the same time the variable index of adherence to the Commedia.